Narodziny terapii filozoficznej z ducha antyku. W kierunku stawania się osobą - Tomasz Femiak (Studia Philosophiae Christianae)
This paper lists the problems that philosophical therapy deals with and tries to provide a definition of philosophical therapy. In particular, we find references to Homeric psychology, contemporary therapeutic trends, and examples of the use of philosophical therapy (observation records after individual sessions of philosophical therapy or group work). This article develops the connections between philosophical therapy and the ancient understanding of philosophy (ancient spiritual exercises). The focal point of our considerations concerns the application of philosophical therapy to the process of becoming a person.